Involvement of young fathers in fatherhood activities - Calma, Francis Ann L.; Trio, Consuelo Q. (2004.)
This study sought to find out the involvement of young fathers in fatherhood activities in relation to their demographic characteristics: age, educational attaintment and income. It also determined the activities young fathers perform with/for their children. Thirty young fathers aged 15-24 from Quezon City were the focus of the study. An interview was conducted from January to March 2004 to determine their level of involvement in fatherhood activities using a checklist. The interview was structured into three parts: informed consent, information sheet and checklist of activities for the interview proper. The activities were classified into weekly, monthly and yearly activities categories. The demographic characteristics were also divided into two groups for comparison of data gathered within the group. Data was analyzed using frequencies, percentages, ranking, and means. Distribution of age, educational attainment and income were summarized by frequency and percentages. The results in overall participation of young fathers were ranked per category. In general, young fathers have high involvement in all fatherhood activities. Playing, cuddling and looking after the child ranked highest while watching movies ranked least among all activities. Young fathers involvement vary from each activity because of some external factors like nature of job, time availability, age of their children, employment of wife and resources at hand.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Fatherhood -- Philippines; Father and child -- Philippnes